PENGARUH GAYA KEPEMIMPINAN DISTRIBUTIF DAN KEPEMIMPINAN KONSULTATIF TERHADAP ETOS KERJA GURU DAN TENAGA KEPENDIDIKAN DI SMAN 10 PANGKEP - Mashuri Adsan; Muh Yunus; Muhammad Fahreza W (STKIP Pesisir Selatan, 2022)
This study aims to determine and analyze: 1) the influence of the distributive leadership style on the work ethic of teachers and education personnel at SMAN 10 Pangkep, (2) the influence of the consultative leadership style on the work ethic of teachers and education personnel at SMAN 10 Pangkep, (3) the influence of leadership styles distributive and consultative leadership on the work ethic of teachers and education personnel at SMAN 10 Pangkep. This type of research is quantitative research. This research was conducted at SMAN 10 Pangkep. The population in this study were teachers and education personnel with a total of 55 respondents. The data analysis technique used is descriptive analysis and multiple linear regression test. The results showed (1) distributive leadership style had a significant effect on the work ethic of teachers and education personnel at SMAN 10 Pangkep, (2) consultative leadership style had a significant effect on the work ethic of teachers and education personnel at SMAN 10 Pangkep, (3) distributive leadership and leadership. simultaneously have a significant effect on the work ethic of teachers and education personnel in SMA 10 Pangkep. The contribution of the influence of the distributive leadership and consultative leadership variables was 20.3% and the remaining 79.7% showed the influence of other variables that were not evaluated in this study.